Internet of Things From Hype to Reality The Road to Digitization - Rayes, Ammar; Salam, Samer (Springer International Publishing : Imprint: Springer, 2019)
This textbook presents an end-to-end Internet of Things (IoT) architecture that comprises of devices, network, compute, storage, platform, applications along with management and security components with focus on the missing functionality in the current state of the art. As with the first edition, it is organized into six main parts: an IoT reference model; Fog computing and the drivers; IoT management and applications ranging from smart homes to manufacturing and energy conservation solutions; Smart Services in IoT; IoT standards; and case studies. The textbook edition features a new chapter entitled The Blockchain in IoT, updates based on latest standards and technologies, and new slide ware for professors. It features a full suite of classroom material for easy adoption.